2022
DOI: 10.3390/ijerph191610379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Distribution of Perfluoroalkyl Substances in Rice Paddy Lysimeter with an Andosol

Abstract: The properties of potential emerging persistent contaminants, perfluoroalkyl substances (PFAS), in an andosol rice paddy lysimeter were analyzed to determine their mobility and leaching behavior regarding carbon chain length and functional groups. For this purpose, simulated contaminated water (ΣPFAS = 1,185,719 ng/L) was used in the lysimeter. The results showed that PFAS distribution in the paddy soil lysimeter was influenced by the migration of these substances into irrigation water and their adsorption int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…As observed previously, despite being industrially used as a short-chain alternative to PFOA, GenX still has similar properties that make it unsafe for the environment. are consistent with the present ooded soil conditions, have determined that due to their high mobility in water, short-chain PFAS like GenX are likely to leach into groundwater systems, thereby reducing their availability for plant uptake (Eun et al 2022). This explains our observation that less GenX accumulated in the shoots of rice grown in ooded soil.…”
Section: Genx Distribution Coe Cientsupporting
confidence: 85%
“…As observed previously, despite being industrially used as a short-chain alternative to PFOA, GenX still has similar properties that make it unsafe for the environment. are consistent with the present ooded soil conditions, have determined that due to their high mobility in water, short-chain PFAS like GenX are likely to leach into groundwater systems, thereby reducing their availability for plant uptake (Eun et al 2022). This explains our observation that less GenX accumulated in the shoots of rice grown in ooded soil.…”
Section: Genx Distribution Coe Cientsupporting
confidence: 85%
“…Andosols (volcanic ash soils) dominate approximately 47% of agricultural land in Japan and are characteristic of a high carbon content . The TC content of the cultivated soil in tthis study was 3.8%, which is typical of Andosol (Figure and Table S5).…”
Section: Resultsmentioning
confidence: 71%
“…Andosols (volcanic ash soils) dominate approximately 47% of agricultural land in Japan and are characteristic of a high carbon content. 44 The TC content of the cultivated soil in tthis study was 3.8%, which is typical of Andosol (Figure 1 and Table S5). A recent review by Lesmeister et al (2021) indicated that the use of organic solvents for soil extraction creates uncertainties in the estimation of bioaccumulation factors.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…Thus, uptake and bioaccumulation does not only depend on GenX properties and chemical characteristics but also on plant species and its capacity for bioaccumulation. As Doucette et al ( 2018 ) noted that the differences in PFAS uptake among species are due to varying biotransformation capacities, rates of dissipation, ease of root uptake and temperature. Further, Zhao et al ( 2016 ) found that uptake of PFCA by wheat increased by 1.5- to 2.3-fold when the temperature increased from 20 to 30 °C.…”
Section: Discussionmentioning
confidence: 99%